Kinerja Keuangan Organisasi Laba - M. Setiadi Hartoko (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
Financial performance was illustrated by the financial ratios of this company. Financial ratios were calculated in this paper only profitability ratios derived from the calculation of the income statement and operational activities in the period of 2013. We used method through library research and field work in getting the data and information needed. The results are,the company is still in good condition and worth for investors to invest in the next few years.